Levels of BDNF and NGF in adolescent rat hippocampus neonatally exposed to methamphetamine along with environmental alterations - Čechová, Barbora; Mihalčíková, Lydia; Vaculín, Šimon; Šandera, Štěpán; Šlamberová, Romana (Physiological research, 2023)
Neurotrophins are proteins included in development and functioning of various processed in mammalian organisms. They are important in early development but as well as during adulthood. Brain - derived neurotrophic factor (BDNF) and nerve growth factor (NGF) have been previously linked with many psychiatric disorders such as depression and addiction. Since during postnatal development, brain undergoes various functional and anatomical changes, we included preweaning environment enrichment (EE), since enrichment has been linked with improved function and development of the several brain structure such as hippocampus (HP), in which we monitored these changes. On the other hand, social isolation has been linked with depression and anxiety-like behavior, therefore postweaning social isolation has been added to this model as well and animal were exposed to this condition till adolescence. We examined if all these three factors had impact on BDNF and NGF levels during three phases of adolescence - postnatal days (PDs) 28, 35 and 45. Our results show that EE did not increase BDNF levels neither in control or MA exposed animals and these results are similar for both direct and indirect exposure. On the other side, social separation after weaning did reduce BDNF levels in comparison to standard housing animals but this effect was reversed by direct MA exposure. In terms of NGF, EE environment increased its levels only in indirectly exposed controls and MA animals during late adolescence. On the other hand, social separation increased NGF levels in majority of animals.
Keywords: methamfetamin; mozkový neurotrofický faktor; nervový růstový faktor; Brain-Derived Neurotrophic Factor; Rats; mozek; Nerve Growth Factor; Animals; Prenatal Exposure Delayed Effects; krysa rodu Rattus; zpožděný efekt prenatální expozice; Hippocampus; zvířata; Brain; hipokampus; Methamphetamine